Criminal Deterrence: A Review of the Literature - Chalfin, Aaron; McCrary, Justin (Journal of Economic Literature, 2017)
We review economics research regarding the effect of police, punishments, and work on crime, with a particular focus on papers from the last twenty years. Evidence in favor of deterrence effects is mixed. While there is considerable evidence that crime is responsive to police and to the existence of attractive legitimate labor-market opportunities, there is far less evidence that crime responds to the severity of criminal sanctions. We discuss fruitful directions for future work and implications for public policy. (JEL J64, K42)